PENGARUH CORPORATE SOCIAL RESPONSIBILITY, PERCEIVED QUALITY DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN ULANG DENGAN CORPORATE IMAGE SEBAGAI VARIABEL INTERVENING STUDI PADA PENGGUNA PRODUK TOLAK ANGIN PT SIDOMUNCUL DI KELURAHAN TEMBALANG SEMARANG - Eka, Noviasari Dewi; Farida, Naili; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
This study aimed to determine the effect of corporate social responsibility, perceived quality and brand image to purchase decisions with the corporate image as an intervening variable. Type of research used in this research is explanatory research with 100 respondents taken using accidental sampling technique. The method of analysis used in this study is using a simple linear regression two – stage with SPSS for windows. The results shows that corporate social responsibility variables, perceived quality and brand image has a positive and significant effect (partial) to the corporate image of each 19,4%, 30.4% and 34,6%. Corporate image variable also has a positive and significant effect (partial) to the purchase decisions of 16, 9%.